(untitled) (Theatrum historiae, 2015)
Using the particular example, the contribution analyzes the defence strategies by means of which, in the early 1630s – in connection with the Saxon invasion of the Czech lands - Bohemian Obristkanzler Wilhelm Slavata attempted to protect his estates on the border of southern Bohemia and southern Moravia both from attacks of enemy troops and the soldiers passing through and staying in seigniorial services.